Defects in the low density lipoprotein receptor gene affect lipoprotein (a) levels: multiplicative interaction of two gene loci associated with premature atherosclerosis. - Utermann, G (1989)
The lipoprotein (a) [Lp(a)] contains two nonidentical protein species, apolipoprotein (apo) B-100 and a specific high molecular weight glycoprotein, apo(a). Lp(a) represents a continuous quantitative genetic trait, the genetics of which are only poorly understood. Genetic variation at the apo(a) locus affects plasma Lp(a) levels and explains at least 40% of the variability of this trait. Lp(a) levels were found to be elevated 3-fold in the plasma from patients with the heterozygous form of familial hypercholesterolemia who have one mutant low density lipoprotein receptor gene. This elevation was not due to a higher frequency of those apo(a) types that are associated with high Lp(a) levels in familial hypercholesterolemia patients. Rather Lp(a) levels were elevated for each of the apo(a) phenotypes examined. The effects of the apo(a) and low density lipoprotein receptor genes on Lp(a) levels are not additive but multiplicative. This is a situation not commonly considered in quantitative human genetics. We conclude that Lp(a) levels in plasma may be determined by variation at more than one gene locus.